FRGS GRANTS 2020 - Mohd Azlan Jayasilan, Abdul Gulam Azad (Universiti Malaysia Sarawak (UNIMAS), 2020)
Approximately 79% of Bornean Durio spp. is found in Sarawak (15 species). However, there are very few attempts to investigate on the relationships of Durio with its primary pollinators, bats (Pteropodidae). This study will focus on investigating the floral biology and pollination strategy of selected native Durio spp. Field observations such as flowering time, period of anthesis, presence of visitors, and confirmation on the role of pollinators will be conducted. Several controlled pollination experiments (open pollination, autogamic pollination, and hand pollination) will be carried out to to confirm Durio breeding system. Molecular phylogenetic analysis will be carried out to investigate the relatedness among Durio spp. and bats separately to determine if there is a correlation among the plant hosts and its pollinators. The project is expected to produce evidence of the dependency of Durio spp. on bats for fruit set success. Therefore understanding wildlife pollinators to an economically important plant species and critical services to the ecosystem, society livelihoods and the mutual relationship are vital for management and conservation of both the mutually dependent spe